THE EFFECT OF QUALITY OF WORK LIFE AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE - Oktafien, Shinta; Oktari, Sari Dewi; Suhardi, Agatha Rinta (LPPM STIE Muhammadiah Bandung, 2023)
Employees who are able to work well are the company's most desirable resources in order to achieve company goals. The purpose of this study was to find out how much influence the quality of work life and work environment have on employee performance at the Regional Secretariat in the Bandung City Government Environment. The population and sample in this study were all employees working at the Regional Secretariat in the Bandung City Government Environment with a total of 261 people. The sampling method in this study is in the form of a saturated sampling method (census) because the sample taken has the same number as the population. Judging from the type of research, this research is included in the causal associative type of research which is a type of research used in order to find out the relationship between the variables studied in a study. Meanwhile, the data processing techniques in this study can be explained in the following ways: descriptive statistics, research instrument testing (validity test, reliability test, and classical assumption test), multiple regression analysis, and hypothesis testing. Based on the results of data processing it was concluded that either partially or simultaneously, there is a significant influence between quality of work life and work environment on employee performance.